Revisiting the colloidal fundamentals of water-dispersible polyesters: interactions and self-assembly of polymer nanoaggregates in water. Issue 11 (28th February 2018) - Islam, Sabina; Inglefield, David L.; Velev, Orlin D.
Abstract : When suspended in water, polyester ionomers self-assemble into soft nanoaggregates, whose colloidal properties can be predicted by classical DLVO theory. Abstract : Water-dispersible sulfopolyesters are a major class of film-forming and solution-modifying polymers, which are routinely used in applications such as inks, adhesives, coatings, and personal care products. Since these polyesters are designed to be used as waterborne dispersions, understanding their colloidal interactions in dispersions is critical for their application. By using a range of commercially available water-dispersible sulfopolyesters as a model system, we investigated the relationship between their molecular composition, colloidal interactions, and phase equilibria. We established how these polyesters undergo different molecular configurations and nanoaggregated states, depending on the nature of the liquid medium. For example, the polyesters are in a solvated molecular form in certain organic solvents, whereas they self-assemble into compact nanoaggregates in water. We found that the interactions of these nanoaggregates follow the classical DLVO theory of critical colloidal coagulation where the stability of these nanoparticles is extremely sensitive to multivalent electrolytes ( i.e., C crit ∝ z −6 ). By using static, dynamic, and electrophoretic light scattering, we correlate their nanoscale intermolecular and interparticle interactions with corresponding macroscale phase behavior in both organic medium and water, based on the theoretical framework of second virial coefficients. We present a model for nanoaggregate formation in water based on the critical surface charge density of these nanoparticles. Such fundamental understanding of colloidal interactions could be used to efficiently control and improve the colloidal stability and film-formation ability of these polyesters and may enable the design of novel high-performance surfactant-free waterborne dispersion systems.